Ureteral Marginal Zone Lymphoma of Mucosa-Associated Lymphoid Tissue, Chronic Inflammation, and Renal Artery Atherosclerosis - Lee, Hojung; Joo, Jong Eun; Hong, Young Ok; Lee, Won Mi; Kim, Eun Kyung; Woo, Jeong Joo; Gong, Soo Jung; Huh, Jooryung (Journal of pathology and translational medicine, 2015)
Unlike its gastric or even bladder counterpart, ureteropelvic MALT lymphoma rarely shows subepithelial lymphoid infiltrates or lymphoepithelial lesions, mainly involving periureteral fat.1,4-8 Thus, ureteral MALT lymphoma is probably not associated with 'mucosa' or luminal insults but rather with periureteral inflammation. [...]in the case of lymphoma accompanied by inflammatory lesion, it may be better to be called 'inflammation-associated lymphoid tissue lymphoma' rather than MALT lymphoma, if MALT is not present, as in this case. [...]atherosclerosis is defined as a chronic inflammatory response of the arterial wall to endothelial injury triggered by a variety of insults including lipid accumulation.10 Many inflammatory cells, mostly monocytes and CD4+T cells, are recruited into the arterial intima, forming atheromatous plaques and accompanied by high blood levels of acute phase reactants such as CRP, as in the present case.10 Renal artery atherosclerosis in our patient may be a coincidental lesion considering his old age. [...]the patient's laboratory and pathologic findings indicated that the inflammatory process was concurrently ongoing within the renal artery and peripelvic adipose tissue. [...]in the present case, the final outcome may manifest as ureteral MALT lymphoma and renal artery atherosclerosis.